Analysis of Clinical Features and Risk Factors in Pregnant Women With Miliary Pulmonary Tuberculosis After In Vitro Fertilization Embryo Transfer - Dong, Siyuan; Zhou, Ruoyu; Peng, Emin; He, Ruoxi (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose Miliary pulmonary tuberculosis (TB) among pregnant women after in vitro fertilization embryo transfer (IVF-ET) causes poor outcomes but is rarely reported. This study analyzed the clinical characteristics and risk factors of these patients to provide hints for further studies. Method The demographic characteristics, clinical manifestations, radiologic features, treatment, and outcomes of six patients diagnosed from May 2012 to August 2021 in Xiangya Hospital and 69 patients that were reported in English or Chinese literature from January 1980 to August 2021 were retrospectively analyzed. Continuous variables were compared between groups by t-test or Mann–Whitney U test, and categorical variables were compared between groups by chi-square test or Fisher exact test. Univariate and multiple logistic regression analyses were used to determine the predictors of respiratory failure. Results A total of 75 patients were included. The average age of patients was about 30 years. All patients had tubal obstruction; 5 of them were diagnosed with pelvic TB before. Thirteen cases had a history of pulmonary or extrapulmonary TB, six out of them without any antituberculosis treatment history. All patients were in their first or second trimester during the onset of symptoms. The average interval between onset of symptoms and radiologic examination was about 21 days. The most common abnormalities on chest computed tomography scan were multiple nodules, pulmonary infiltrate, and consolidation. Merely 10 patients obtained bacteriological diagnosis by Mycobacterium tuberculosis culture or polymerase chain reaction test. The other patients were clinically diagnosed. All the patients received antituberculosis treatment. Although 44% of patients had fatal complications, all cases were cured or improved after antituberculosis treatment. Unfortunately, only eight fetuses survived (10.6%). The most frequent and severe complication was type I respiratory failure (20%). Patients with expectoration, dyspnea, coarse breath sounds, ground-glass opacity, and pulmonary infiltrate or consolidation were more likely to have respiratory failure (P < 0.05). Ground-glass opacity (OR = 48.545, 95% CI = 2.366–995.974, P = 0.012) and pulmonary infiltrate or consolidation (OR = 19.943, 95% CI = 2.159–184.213, P = 0.008) were independent predictors for respiratory failure. Conclusion Tube infertility with underscreened or untreated TB is a risk factor for miliary TB during pregnancy after IVF-ET. Ground-glass opacity and pulmonary infiltrate or consolidation are predictors of respiratory failure. We demonstrate risk factors for incidence and complications to supply clues for future intervention and improve patient prognosis.